Satisfying Missouri’s Perpetuity Rules - Merle E. Brake (Washington University Law Quarterly, 1952)
Satisfying the so-called perpetuity rules enjoys the undeserved reputation of being one of the most troublesome problems encountered in designing transfers of property. Although the learning about such rules may seem intricate and confusing, this is due, not to any complexities inherent in the rules themselves, but rather to the construction problems so often associated with the application of such rules, and to the confusion necessarily incident to the explorations of the courts as they seek to determine the objectives, the operational areas, and the permissible period of such rules. From the standpoint of the draftsman of a deed or a will, the perpetuity rules seldom present serious difficulties once they are clearly defined in the law. Usually a conveyor's scheme for the disposition of his property is safely within the confines of the perpetuity rules. Sometimes his plans are so ambitious that they overstep these bounds, and must be changed accordingly.
Keywords: Perpetuities